Perceptual models of uncertainty for socio-hydrological systems: a flood risk change example. Issue 11 (18th August 2017) - Westerberg, Ida K.; Di Baldassarre, Giuliano; Beven, Keith J.; Coxon, Gemma; Krueger, Tobias
ABSTRACT: Characterizing, understanding and better estimating uncertainties are key concerns for drawing robust conclusions when analyzing changing socio-hydrological systems. Here we suggest developing a perceptual model of uncertainty that is complementary to the perceptual model of the socio-hydrological system and we provide an example application to flood risk change analysis. Such a perceptual model aims to make all relevant uncertainty sources – and different perceptions thereof – explicit in a structured way. It is a first step to assessing uncertainty in system outcomes that can help to prioritize research efforts and to structure dialogue and communication about uncertainty in interdisciplinary work.